Analisis Miskonsepsi Siswa Kelas V Materi Ekosistem Menggunakan Four Tier Diagnostic Test - Dewi Septiana; Fina Fakhriyah; Sri Sulisyorini (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the misconceptions of fifth-grade students on the ecosystem material. This study uses a descriptive method with a quantitative research type. The sample of this study was class V students in the 2024/2025 academic year with a total of 19 students. The data collection technique used a four-tier diagnostic test instrument in the form of multiple-choice questions on the ecosystem material as many as 10 questions, accompanied by the reasons for the answers given and the level of confidence of the answers given in three levels: sure, not sure, and guessing. The data analysis technique used in this study is descriptive quantitative by finding the percentage of student misconceptions in each question indicator. From the results of the study after conducting the four-tier diagnostic test, data on student misconceptions on the ecosystem material was obtained with significant findings on abiotic components. The highest misconception occurred in question number 1 regarding the definition of the ecosystem, where students separated abiotic components from the ecosystem system. This is caused by students' literal understanding that ecosystems only involve living things. The results of this study are expected to be a basis for teachers in designing more effective learning strategies, such as conceptual change approaches, to minimize student misconceptions.